2004
DOI: 10.1074/jbc.m406856200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with Transducin Depletes Metarhodopsin III

Abstract: In the phototransduction pathway of rhodopsin, the metarhodopsin (Meta) III retinal storage form arises from the active G-protein binding Meta II by a slow spontaneous reaction through the Meta I precursor or by light absorption and photoisomerization, respectively. Meta III is a side product of the Meta II decay path and holds its retinal in the original binding site, with the Schiff base bond to the apoprotein reprotonated as in the dark ground state. It thus keeps the retinal away from the regeneration path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…The concept of lipidic substances as full or partial ligand agonists is not novel. For (44) adjusted to highlight our experimental conditions. After initial photoactivation, an equilibrium between Meta-I and Meta-II rhodopsin is established within milliseconds.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of lipidic substances as full or partial ligand agonists is not novel. For (44) adjusted to highlight our experimental conditions. After initial photoactivation, an equilibrium between Meta-I and Meta-II rhodopsin is established within milliseconds.…”
Section: Discussionmentioning
confidence: 99%
“…Spectroscopic data show that blue light absorption of the active Meta II state does not lead back to the ground state ( max Ï­ 500 nm) to a significant extent but to a product with an absorption maximum at 475 nm (32). By UV-visible and FTIR difference spectroscopy, this blue light-induced photoproduct of Meta II could be identified as Meta III (33,34), a species already known as a side product of the thermal Meta II decay (9). Recent work has shown that this thermal product contains the chromophore in the Schiff base all-trans-15-syn configuration (35) and that the Meta III formed by light absorption is the same by all available criteria.…”
mentioning
confidence: 99%
“…The end product of the new light-induced pathway, Meta III, can form up to 80%, depending on the conditions, and has remarkable properties. Because of its long lifetime (up to hours (34)), it excludes the chromophore very efficiently from the regeneration pathway, which has led to the concept of a retinal storage form (34,37,38). Remarkably, the lifetime of Meta III depends on the presence of G-protein (34) and arrestin (39,40), which was interpreted as an "inverse catalysis" of receptor conversion by G-protein.…”
mentioning
confidence: 99%
See 2 more Smart Citations